From modern humans to the advent of writing - Cardoso, João Luís (2022)
The essays which follow, covering the Prehistory and Protohistory of the territory which is nowadays Portugal, result from critical discussion of key themes associated with the two major periods prior to the introduction of writing (Prehistory) or contemporary with the first societies to adopt writing in the Western Península (Protohistory).